ANALYSIS OF THE RESPONSE OF THE BALTIC COUNTRIES TO THE CONFLICT BETWEEN RUSSIA AND UKRAINE - Nindya Raihan Zani; Sherina Oktavia; Jihan Tiara Salsabila; Rihhadatul Aisya; Sonia Pesliko (International Journal Labs, 2022)
This study aims to see the response of the Baltic countries in dealing with the Russia-Ukraine conflict through their foreign policies, where these countries are part of the European Union. The baltic countries also felt a significant impact due to the heating up of relations between the two countries. The Baltic states consisting of Lithuania, Latvia and Estonia gave some of their responses to the Russo-Ukrainian conflict by strengthening cooperative relations with NATO. This response is a form of the security dilemma experienced by the Baltic countries. The response of other Baltic countries is also shown by several foreign policies such as stopping the import of Russian gas into their country. Even though their country is very dependent on Russia for their domestic gas energy needs. This dynamic will be discussed in this research using related theories and concepts. This study uses a qualitative method by obtaining data from related sources such as official websites, journals, news portals and official documents from related institutions.